The Cytotoxic Evaluation of Steroids Isolated from Dysoxylum alliaceum (Blume) Blume ex A.Juss. - Riyadi, Sandra Amalia; Naini, Al Arofatus; Mayanti, Tri; Lesmana, Ronny; Azmi, Mohamad Nurul; Supratman, Unang (Molekul, 2024)
Dysoxylum alliaceum belongs to the Dysoxylum genus (Meliaceae) and there are few reports concerning the phytochemical components of this plant. To examine the chemical constituents of Dysoxylum alliaceum stem bark, a phytochemical study has been conducted and identified five known steroids, 3β,16β-dihydroxy-24(S)-methyl cholestenol (1), ergosta-5,22-dien-3β-ol (2), ergosta-7,24(28)-dien-3β-ol (3), 22(E)-ergosta-6,22-dien-3β,5α,8α-triol (4), and 20α-dihydroprogesterone (5) from its ethanolic extract. Spectroscopic data such as FT-IR, HR-ESI-MS, 1D, and 2D NMR as well as comparison with previously published spectral data were used to identify the chemical structures of compounds 1–5. Furthermore, these steroids 1-5 were assessed in vitro regarding their cytotoxic effect against A549 lung cancer cell lines and revealed weak to inactive with IC50 values ranging from 68.52 to >150 µM. Keywords: A549 cell lines, cytotoxic evaluation, Dysoxylum alliaceum (blume) blume ex a.juss, meliaceae, steroid